DAMPAK SERTIFIKASI TERHADAP KOMPETENSI PEDAGODIK GURU (STUDI PEMETAAN (PK) GPAI ON-LINE TINGKAT SMA/SMK WILAYAH SERANG TIMUR - Riyadi, Toton (STAI Darul Qalam Tangerang, 2021)
Certification is one of the breakthroughs to improve teacher professionalism. This means that if the teacher's competence is good, the teacher's performance will also be good. Certification should not be used as an arena for economic improvement, but an arena for increasing professional competence in teaching. So that certified teachers are teachers who are professional in educating their students. The problem of this research is the impact of PAI SMA / SMK teacher certification on pedagogical competence (online PK value assessment). Therefore this study aims to determine the impact of certification on the pedagogy of high school teachers in the East Serang Region, which includes Pedagogical 1 (painful learning), Pedagogical 2 (learning model), and Pedagogical 3 (learning assessment). is a qualitative descriptive study. The subjects in this study were certified teachers in the East Serang Region and the data were used through data documentation. From this research it can be concluded that the implementation of certification was followed by certified teachers in the East Serang region which is under the auspices of the Ministry of Religion. There are 219 teachers who have been certified both PNS and non PNS who have been accepted by the Ministry of Religion and the Ministry of Education in the East Serang Region. Teacher performance before certification cannot be measured. After the PAI teacher competency mapping activity, it was seen the competence of PAI teachers and Character in the East Serang Region